On the quasi-yield surface concept in plasticity theory - Soldatos, Dimitris; Triantafyllou, Savvas P. (Wiley-VCH Verlag, 2017)
In this paper we provide deeper insights into the concept of the quasi-yield surface in plasticity theory. More specifically, in this work, unlike the traditional treatments of plasticity where special emphasis is placed on an unambiguous definition of a yield criterion and the corresponding loading-unloading conditions, we place emphasis on the study of a general rate equation which is able to enforce elastic-plastic behavior. By means of this equation we discuss the fundamental concepts of the elastic range and the elastic domain. The particular case in which the elastic domain degenerates into its boundary leads to the quasi-yield surface concept. We exploit this concept further by discussing several theoretical issues related to it and by introducing a simple material model. The ability of the model in predicting several patterns of the real behavior of metals is assessed by representative numerical examples.